Penentuan Urutan Prioritas Penanganan Pemeliharaan Jembatan Ruas Jalan Nasional di Pulau Bangka Provinsi Kepulauan Bangka Belitung - Rakhmatika, Rakhmatika; Setiadji, Bagus Hario; Riyanto, Bambang (MEDIA KOMUNIKASI TEKNIK SIPIL, 2017)
Bridge is a part of road infrastructure system which must be well managed. One of the maintenance strategy is a whole year maintenance to keep the bridge in good condition during its design life. With tight budget, a comprehensive decision is needed to prioritize which bridge needed the most. The purpose of this research is to identify and determining the criteria and sub criteria, the scale of priority handling, and value sensitivity in maintenance activities bridge in of national roads island bangka. Analytical Hierarchy Process (AHP) was used to provide qualitative space for experts to share opinions and complemented with quantitative analysis. This method was also as an applicative tool to support BMS (Bridge Management System) program by using more measurable approach. This research used six criteria and 18 sub-criteria. The criteria with the highest and lowest weight were general condition of the bridge and social and regional development aspect, respectively, while the sub-criteria with the highest and lowest weight were watershed condition and the number of public facilities served, respectively. The resulst on 74 researched bridges showed that Segambir bridge became the bridge with the most priority to be maintained, followed by Birah and Nangka bridges.